Lower leg muscle-tendon unit characteristics are related to marathon running performance - Kovács, B.; Kóbor, I.; Gyimes, Z.; Sebestyén, Ö.; Tihanyi, J. (Scientific Reports, 2020)
The human ankle joint and plantar flexor muscle-tendon unit play an important role in endurance running. It has been assumed that muscle and tendon interactions and their biomechanical behaviours depend on their morphological and architectural characteristics. We aimed to study how plantar flexor muscle characteristics influence marathon running performance and to determine whether there is any difference in the role of the soleus and gastrocnemii. The right lower leg of ten male distance runners was scanned with magnetic resonance imagining. The cross-sectional areas of the Achilles tendon, soleus, and lateral and medial gastrocnemius were measured, and the muscle volumes were calculated. Additional ultrasound scanning was used to estimate the fascicle length of each muscle to calculate the physiological cross-sectional area. Correlations were found between marathon running performance and soleus volume (r = 0.55, p = 0.048), soleus cross-sectional area (r = 0.57, p = 0.04), soleus physiological cross-sectional area (PCSA-IAAF r = 0.77, p < 0.01, CI± 0.28 to 0.94), Achilles tendon thickness (r = 0.65, p < 0.01), and soleus muscle-to-tendon ratio (r = 0.68, p = 0.03). None of the gastrocnemius characteristics were associated with marathon performance. We concluded that a larger soleus muscle with a thicker Achilles tendon is associated with better marathon performance. Based on these results, it can be concluded the morphological characteristics of the lower leg muscle-tendon unit correlate with running performance.